First Principle Computational Studies On The Electronic Structure Of Muonated Κ-(Bedt-Ttf)2Cu[N(Cn)2]Cl And Κ-D8-(Bedt-Ttf)2Cu[N(Cn)2]Br - Hasan Baseri, Dang Fatihah (2022)
κ --(BEDT TTF) R 2 R Cu[N(CN) R 2 R ]Cl and κ-d8-(BEDT-TTF)R2RCu[N(CN)R2R]Br are organic magnet material s with potential application in spintronics. The number of µ SR data on this structure ha s increas ed r apidly and continuously appear from time to time. An unpaired electron is generally localized throughout the dimer and is not localized around a particular atom which can affect the ma gnetic properties of the system . the long range ordering of the magnetic moments that was configured by the m agnetic structure of the system remains unclear and further investigations are required. In order t o complement the µ SR study , the Density Functional Th eory (DFT) computational me thod has been performed to investigate the electronic structures in the high spin and antiferromagnetic ( AFM state as well as to observe the type of the magnetism that exists in this compound. As the total energy obtained in an AFM state for MMR1212R, MMR2323R and M 31 configurations are slightly more stable compared to the high spin state, it is computationally proved that the ground state possessed an AFM configuration . The relative energy for